Psychologic-Pedagogical Principles of Primary School Pupils’ Connected Speech Development - Nataliya Savchuk (Pedagogical Discourse, 2012)
The essentiality of primary school pupils’ connected speech is reaveled, and psychologically-pedagogical principles of connected speech development are described in the article.